2022
DOI: 10.2169/internalmedicine.9437-22
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Mycosis Complicated with Lung Adenocarcinoma

Abstract: Chest computed tomography (CT) of a 76-year-old woman with bronchial asthma showed multiple lung nodules with high CT densities that were compatible with high-attenuation mucoid (HAM) impactions characteristic of allergic bronchopulmonary mycosis (ABPM). Follow-up chest CT revealed increased sizes of multiple lung nodules. However, a left upper lobe nodule showed lower CT density than the other HAM impactions. A transbronchial lung biopsy of that upper lobe nodule revealed lung adenocarcinoma. Measuring the CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“… 20 , 21 Serum CEA levels have long been recognized as potential biomarkers for diagnosing tumors, monitoring tumor progression, and post-surgical surveillance in various cancer types, such as breast cancer and gastrointestinal tumors. 5 7 Ohnishi et al 22 reported a patient exhibited elevated CEA and EOS levels, which led to the detection of malignancy, and was subsequently diagnosed as allergic bronchopulmonary mycosis complicated with lung adenocarcinoma. However, elevated CEA levels have also been reported in benign conditions.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“… 20 , 21 Serum CEA levels have long been recognized as potential biomarkers for diagnosing tumors, monitoring tumor progression, and post-surgical surveillance in various cancer types, such as breast cancer and gastrointestinal tumors. 5 7 Ohnishi et al 22 reported a patient exhibited elevated CEA and EOS levels, which led to the detection of malignancy, and was subsequently diagnosed as allergic bronchopulmonary mycosis complicated with lung adenocarcinoma. However, elevated CEA levels have also been reported in benign conditions.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The most important particularity of our case is the association between colonization with Aspergillus and two synchronous tumors. After reviewing the scientific literature, we found several cases of associations between pulmonary aspergillosis and carcinoid tumors, as well as pulmonary aspergillosis and pulmonary adenocarcinoma [ 27 , 28 , 29 , 30 , 31 ]. However, we have not discovered any cases that linked all three diseases.…”
Section: Discussionmentioning
confidence: 99%